What determines customers’ loyalty towards telecommunication service? mediating roles of satisfaction and trust - Hiram, Ting; Tan, Kim Lim; Lim, Xin Jean; Cheah, Jun Hwa; Ting, Qian Hui; Ting, Hui Bun (Inderscience Publishers, 2020)
The purpose of this study is to: 1) examine the effects of corporate image, pricing, service quality and network quality on customer loyalty in the Malaysian mobile telecommunications sector; 2) to determine the mediating effects of customer satisfaction and trust. The study's hypotheses were tested using partial least squares structural equation modelling (PLS-SEM). In total, 388 respondents participated in this study. Our findings revealed that network quality and corporate image exert a positive effect on customers' satisfaction and trust which in turn influence customers' loyalty. In addition, the mediation results showed that both trust and satisfaction mediate the relationship between network quality and loyalty as well as between corporate image and loyalty. Thus, it is recommended that telecommunications service providers in Malaysia should further improve on their network coverage and corporate image to effectively address the needs of their customer base and ultimately retain its loyalty.